Kriteria Baru Mabims 3-6,4: Upaya Penyatuan Kalender Hijriah di Indonesia Dalam Perspektif Maqāṣid Al-Syarī'ah - Moh. Fadllur Rohman Karim; Mahsun Mahsun (Astroislamica: Journal of Islamic Astronomy, 2024)
Minister of Religion Brunei Indonesia Malaysia Singapore which is abbreviated to MABIMS. Several things have been agreed upon by the ministers of religion from the four countries, including the criteria for imkān rukyat. The MABIMS criteria regarding the new moon have undergone several changes. The new MABIMS criteria or MABIMS hilal neo-visibility are a hilal height of 3⁰ and an elongation of 6.4⁰. These new criteria are applied to unite Muslims, especially in Indonesia, in the Hijri calendar. The author understands that there is something interesting about the neo-visibility of the MABIMS hilal in the form of a maqāṣid al-syarī'ah perspective. This study is from a point of view that is still related to fiqh considering the connection between the neo-visibility of the MABIMS new moon in determining rukyatulhilal. The author found that the MABIMS hilal neo-visibility criteria are from the perspective of maqāṣid al-syarī'ah or the objectives of the shari'a. Maqāṣid al-syarī'ah regarding the criteria for the neo-visibility of the new moon MABIMS related to ḥifẓ al-dīn in the categorization of ḥajiyat with consideration of the impact that will occur in efforts to unify the Hijri calendar not to the level of eliminating souls, changing the order of worship itself and destroying natural sustainability, which is more about setting prayer times, not the essence of worship. The government's efforts in adopting these new criteria are none other than an effort to avoid difficulties and difficulties in the context of Muslim harmony and togetherness as well as strengthening the sense of brotherhood.